CO2 Dispersion Consequences Study using 3D CFD method in a CCUS facility - BRIM ERNESTO KACARIBU (President University, 2022)
CO2 Dispersion Consequences Study using 3D CFD method in a CCUS facility Abstract Carbon Capture Utilization and Storage (CCUS) is a method and technology for CO2 gas injection that enables the capture and storage of CO2 underground. The aim is the CO2 emission reduction into the atmosphere as well as enhancing oil/gas/heat recovery. Unlike their counterparts in USA and Europe, however, the CCUS technology in China is not yet mature or still at a pilot scale. Given the large quantities and flow rates which will be used for CCUS, consequently, major releases could produce significant hazard ranges at concentration high enough to have toxic effects. This paper focuses on the consequence of CO2 releases to the neighbourhood or environment which varies in elevations to study the effect to the varied ground levels from the release points to the extent of CO2 dispersion. The effect of large equipment to the CO2 concentration extents is also discussed.